Poland daily : economy, work, consumption and social class in Polish cinema - Mazierska, Ewa (2017)
Introduction – Interwar cinema: striving for social promotion – The 1920s: the cult of the body and the machine – The 1930s: the beauty and sadness of the room at the top – The cinema in people's Poland: taking a great leap – The 1950s: holy work? – The 1960s: industrial expansion and small stabilisation – The 1970s: bad work and good life – The 1980s: between refusal to work and alienation of labour – Postcommunist cinema: from triumphant neoliberalism to accumulation by – Dispossession – The 1990s: heroic neoliberalism or everybody can be a winner – The 2000s and beyond: accumulation by dispossession